Periodic solutions of strongly nonlinear systems with nonclassical right-hand side in the case of a family of generating solutions - Akhmetov, M. U. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The problem of the existence of periodic solutions to differential equations with pulse effects on the surfaces and to differential equations with discontinuous right-hand sides close to arbitrary nonlinear ones is studied. The existence of a family of periodic solutions to generating equations is assumed.